Use of Modern Pedagogical Technologies in the Training of Drivers - Kudayberganovich, Xakimov Shaukat; Gaffarovich, Samatov Rustam; Anvarovna, Abdurazzakova Dildora (European Journal of Life Safety and Stability (2660-9630), 2022)
The article focuses on the role of innovative technologies in the organization of the educational process of driver training, the introduction of modern pedagogical technologies to education, the important and positive aspects of their use, and the possibilities of modern education in the professional training of drivers.